THE RELATIONSHIP BETWEEN SELF-EFFICACY AND EMOTIONAL REGULATION IN STUDENTS IN TEACHING AND EDUCATION FACULTY AT SYIAH KUALA UNIVERSITY - Bustamam, Nurbaity; Bakar, Abu; Amelia, Riska (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2024)
Emotion regulation is an individual's ability to assess, manage, and express emotions appropriately in order to achieve emotional balance. One of the factors influencing emotion regulation is self-efficacy. People who are confident in their abilities tend to have better control over their emotions. The purpose of this study was to reveal the explanation and relationship between self-efficacy and emotional regulation in final-year students of the Faculty of Teacher Training and Education, Syiah Kuala University. The study population was students of the Faculty of Teacher Training and Education, Syiah Kuala University who were completing the final project of the class of 2019, and the number of samples was 270 out of a population of 829. The sampling method in this study used probability random sampling. The value of the correlation coefficient r = 0.635 explains the strong correlation between self-efficacy and emotional regulation in college students.ABSTRAKRegulasi emosi merupakan kemampuan individu dalam menilai, mengelola, dan mengekspresikan emosi secara tepat guna mencapai keseimbangan emosi. Keyakinan pada diri sendiri atau efikasi diri merupakan salah satu faktor yang mempengaruhi regulasi emosi. Orang yang percaya diri dengan kemampuannya cenderung memiliki kendali yang lebih baik terhadap emosinya. Penelitian ini dilakukan dengan tujuan untuk mengungkap penjelasan dan hubungan antara efikasi diri dengan regulasi emosi pada mahasiswa tingkat akhir FKIP Universitas Syiah Kuala. Populasi penelitian adalah mahasiswa dari seluruh fakultas di Universitas Syiah Kuala yang sedang menyelesaikan tugas akhir yakni angkatan 2019, dan jumlah sampel adalah 270 dari populasi sebanyak 829. Metode pengambilan sampel pada penelitian ini menggunakan probabilitas random sampling. Nilai koefisien korelasi r = 0,635 menjelaskan kuatnya korelasi antara efikasi diri dengan regulasi emosi pada mahasiswa.